Binding of the angiogenic/senescence inducer CCN1/CYR61 to integrin α6β1 drives endocrine resistance in breast cancer cells - Espinoza, Ingrid (2022)
CCN1/CYR61 promotes angiogenesis, tumor growth and chemoresistance by binding to its integrin receptor αvβ3 in endothelial and breast cancer (BC) cells. CCN1 controls also tissue regeneration by engaging its integrin receptorα6β1 to induce fibroblast senescence. Here, we explored if the ability of CCN1 to drive an endocrine resistancephenotype in estrogen receptor-positive BC cells relies on interactions with either αvβ3 or α6β1. First, we tookadvantage of site-specific mutagenesis abolishing the CCN1 receptor-binding sites to αvβ3 and α6β1 to determine theintegrin partner responsible for CCN1-driven endocrine resistance. Second, we explored a putative nuclear role ofCCN1 in regulating ERα-driven transcriptional responses. Retroviral forced expression of a CCN1 derivative with asingle amino acid change (D125A) that abrogates binding to αvβ3 partially phenocopied the endocrine resistancephenotype induced upon overexpression of wild-type (WT) CCN1. Forced expression of the CCN1 mutant TM,which abrogates all the T1, H1, and H2 binding sites to α6β1, failed to bypass the estrogen requirement foranchorage-independent growth or to promote resistance to tamoxifen. Wild-type CCN1 promoted estradiol-independent transcriptional activity of ERα and enhanced ERα agonist response to tamoxifen. The α6β1-binding-defective TM-CCN1 mutant lost the ERα co-activator-like behavior of WT-CCN1. Co-immunoprecipitation assaysrevealed a direct interaction between endogenous CCN1 and ERα, and in vitro approaches confirmed the ability ofrecombinant CCN1 to bind ERα. CCN1 signaling via α6β1, but not via αvβ3, drives an endocrine resistance phenotypethat involves a direct binding of CCN1 to ERα to regulate itstranscriptional activity in ER+ BC cells.